2017
DOI: 10.1016/j.jue.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Housing choices and labor income risk

Abstract: I show that individuals whose unemployment risk tends to increase more when local home prices fall optimally invest less in owner-occupied housing. Using a unique, Swedish register-based database, I …nd that a one standard deviation increase in the covariance between individually estimated unemployment risks and local home prices implies an average increase in the value of households' investments in owner-occupied housing of USD 13,300. Further, I …nd, in line with the predictions of my theoretical model, that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…He found that the self-employed are more satisfied with their jobs, however, there were also indications that self-employment increases mental health problems, in particular, tiredness. But despite all these pieces of research, there are not enough hints to be able to clearly assert that there is a real relationship between entrepreneurship and wellbeing, and to what extent, in clear and specific terms On the other hand, when analysing wellbeing, it is also found that it is an especially relevant issue for women, particularly when it comes to setting up a new business (Ahl & Nelson, 2015;Cervelló-Royo et al 2015, 2017Henry et al, 2015;).…”
Section: Blinded Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…He found that the self-employed are more satisfied with their jobs, however, there were also indications that self-employment increases mental health problems, in particular, tiredness. But despite all these pieces of research, there are not enough hints to be able to clearly assert that there is a real relationship between entrepreneurship and wellbeing, and to what extent, in clear and specific terms On the other hand, when analysing wellbeing, it is also found that it is an especially relevant issue for women, particularly when it comes to setting up a new business (Ahl & Nelson, 2015;Cervelló-Royo et al 2015, 2017Henry et al, 2015;).…”
Section: Blinded Manuscriptmentioning
confidence: 99%
“…Based on self-reported life satisfaction surveys,Fleche et al (2011), show how, apart from income, other indicators like not being unemployed and social relationships are very important for wellbeing with few differences across OECD countries. Several studies consider employment indicators like jobs security(Jansson, 2017;Renee Baptiste, 2008) as indicators of strong influence over wellbeing Osberg & Sharpe (2009),. propose several wellbeing indicators for selected OECD countries, considering not only household income and expenditure aspects but also those related to job security and or employment/unemployment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The literature has shown that households hedge labor income risk by adjusting risky asset holdings (Betermier et al, 2012); and respond to comovement between unemployment and house price risk by reducing investment in owner-occupied housing (Jansson, 2017). In our first application, we consider a related portfolio choice problem, where a worker has obtained a job and must now choose housing; however, rather than selecting a quantity of housing or deciding whether to switch to the rental market, the homeowner will instead choose a location in which to purchase a home.…”
Section: Location Choicementioning
confidence: 99%
“…However, by gaining greater experience over time, necessity-driven entrepreneurs feel less distressed since the crucial psychological needs of being employed are satisfied (Nikiforou et al, 2019). The literature suggests that there is a strong link between employment (or unemployment) and a country's entrepreneurship activity (Jansson, 2017). In necessity-driven entrepreneurship, push factors in the form of high unemployment rates, limited alternative employment opportunities and a lack of or inappropriate employment protection increase the intensity of entrepreneurship in an economy (Block et al, 2015a;Dana, 1997).…”
Section: Necessity-driven Entrepreneurshipmentioning
confidence: 99%